A STUDY ON INVESTMENT BEHAVIOUR OF INDIVIDUAL INVESTORS WITH REFERENCE TO BENGALURU - KUMAR, THINESH (International Journal of Psychosocial Rehabilitation, 2020)
Investment is used for productive purposes and it has a great prominence for being the crucial instrument for economic growth and development of a country. There are many investment avenues are opened today, some of them are direct equity, commodity and derivatives, debt, mutual fund, real estate and gold. Some of the investment instruments are highly risky whereas others are riskless. The behaviour of investors are influenced by many factors during the rational selection of investment such as attitudes, awareness, perception and willingness. An investor is a person who sacrifices the present in order to earn the benefit for the future. The benefits in the form of dividends, capital appreciation, retirement benefits, bonus and other benefits. This study is designed as an extension to the existing body of knowledge and fills the gap for analyzing the individual investment behaviour. The present study is done using a questionnaire for assessing the determinants of investment behaviour of individual investors. The statistical tool, ANOVA, Chi-square and Independent sample T-test, is used in for the study. The study concludes that the majority of the investor prefer to save money and the investor invest with the motto of safety. Professional bodies influence investors in investment decisions. Investors need to consult with the financial advisors for the investment decision.